Baalsaurus mansillai gen. et sp. nov. a new titanosaurian sauropod (Late Cretaceous) from Neuquén, Patagonia, Argentina - CALVO,JORGE O. (2019)
Abstract We describe a dentary of a new titanosaur sauropod, Baalsaurus mansillai, gen. et sp. nov. from the Late Cretaceous of Patagonia, Argentina. The material comes from the Portezuelo Formation, Neuquén Group. Titanosaur sauropods lower jaws are scarce and only nine taxa with dentaries have been described. There are two types of morphology in titanosaur dentaries; “L” shaped or “U” shaped based on the shape, without a phylogenetic issue. In this paper; we recognize a new taxa, Baalsaurus mansillai, represented by an “L” shaped dentary with three apomorphic characters that are not present in other taxa: dentary alveoli with 10 teeth in the anterior ramus, a ventrally and anteriorly inclined symphysis and a wide ventral Meckelian groove surrounded by a thin lamina that forms a keel on the ventral border of the dentary.